Navigated focal laser photocoagulation for central serous chorioretinopathy - Chhablani, Jay (Dove Medical Press, 2014)
BACKGROUND AND OBJECTIVE: To assess the efficacy of navigated laser (Navilas(®)) treatment for central serous chorioretinopathy. MATERIALS AND METHODS: Prospective study included 16 eyes of 15 subjects with nonresolving central serous chorioretinopathy. Fluorescein-angiography guided Navilas(®) treatment was performed. Pre- and posttreatment best-corrected visual acuity, pre- and posttreatment central macular thickness, number of leaks on fluorescein angiography, and various treatment parameters were analyzed. Pain experience was evaluated using the visual analog pain scale. RESULTS: Sixteen eyes from 15 subjects (mean age 42.2±9.9 years) were analyzed. Mean duration of symptoms was 11.45±6.6 months. Average number of leaks per eye was 2.8 and one laser spot per leak was performed. There was complete resolution of subretinal fluid in 15 out of 16 eyes at 2 months. Average visual analog pain scale score was 0.63±1.41. CONCLUSION: Navilas(®) without a contact lens achieved resolution of subretinal fluid with a single laser spot for each single leak and minimum iatrogenic damage.